Durable superhydrophobic/highly oleophobic coatings from multi-dome SiO2 nanoparticles and fluoroacrylate block copolymers on flat substrates1. Issue 40 (28th October 2015) - Junyan, Liang; Li, Wang; Jingxian, Bao; Ling, He
<x xml:space="preserve">Abstract</x> The preparation of (a) multi-dome hydrophobic SiO2 NPs, (b) fluoroalkylsilane-modified SiO2 NPs and (c) superhydrophobic/highly oleophobic coating.